1996
DOI: 10.1074/jbc.271.39.24226
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Conserved and Functional Iron-responsive Element in the 5′-Untranslated Region of Mammalian Mitochondrial Aconitase

Abstract: IREs are RNA stem loop sequences found in the 5Ј-UTR 1 of the mRNAs for ferritin and erythroid amino-levulinic acid synthetase and the 3Ј-UTR of transferrin receptor where they function as a binding site for iron regulatory proteins (IRPs) (reviewed in Refs. 1-3). The two known IRPs, IRP1 and IRP2, bind IREs with equal and high affinity and mediate translational repression of transcripts containing ferritin IREs with equal efficacy (4). IRP1 is a bifunctional protein that also functions as cytosolic aconitase,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
86
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
5

Relationship

4
6

Authors

Journals

citations
Cited by 137 publications
(93 citation statements)
references
References 28 publications
7
86
0
Order By: Relevance
“…The lower stem serves as an additional regulatory element in that its length and G-C content fine-tune the stability of the IRE, modulating the sensitivity of a transcript to IRP-mediated translational control. This model is supported by studies showing that the translation of ferritin is more sensitive to changes in cellular iron status than mitochondrial aconitase, which has a shorter, A-U rich lower stem in its IRE (46).…”
Section: Characteristics For Ires Containing Hhcs Mutationsmentioning
confidence: 80%
“…The lower stem serves as an additional regulatory element in that its length and G-C content fine-tune the stability of the IRE, modulating the sensitivity of a transcript to IRP-mediated translational control. This model is supported by studies showing that the translation of ferritin is more sensitive to changes in cellular iron status than mitochondrial aconitase, which has a shorter, A-U rich lower stem in its IRE (46).…”
Section: Characteristics For Ires Containing Hhcs Mutationsmentioning
confidence: 80%
“…IRPs also regulate enzymes involved in cellular energy homeostasis such as ACO2 and succinate dehydrogenase (SDH) (32,39,40). We found that EPI or NE enhanced binding of IRP to the IREs present in the TfR1 3Ј-UTR to increase its transcript stability (Fig.…”
Section: Discussionmentioning
confidence: 93%
“…Given that 1) aconitases catalyze the interconversion of citrate to isocitrate and thus require the presence of substrate to function, 2) aconitase function in the citric acid cycle is more ancient than a direct role of the protein in iron metabolism, 3) eukaryotic cells need to regulate intermediary metabolism both in the mitochondria and in the cytosol, utilizing citrate and isocitrate for different purposes in each compartment, 4) IRP1 control of the citric acid enzyme mitochondrial aconitase is present in mammalian cells (54,55), and 5) the IRE of Fer1HCH is contained in an alternatively spliced exon, enabling a bypass of IRP-1A-dependent regulation of ferritin (29,30), we speculate that the initial IRE evolved in succinate dehydrogenase subunit B. After generation by gene duplication of two cytosolic aconitases, one of them acquired the ability to bind to the succinate dehydrogenase subunit B transcripts, which would down-regulate the citric acid cycle and secure higher citrate availability for the cytosol.…”
Section: Discussionmentioning
confidence: 99%